Playstation mobile development cookbook : over 65 recipes that will help you create and develop amazing mobile applications! - Fleischauer, Michael (Packt Pub., 2013)
Written as a series of engaging and practical recipes, this essential Cookbook has been meticulously designed and reviewed in order to provide you with the ultimate reference for PlayStation®Mobile development.If you've got some prior experience with C# and want to create awesome projects for the PlayStation®Vita and PlayStationTMCertified devices, then this book is for you.